2017
DOI: 10.1063/1.4985975
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature magnetoresistance of GaSb whiskers

Abstract: Transverse and longitudinal magnetoresistancies in n-type GaSb whiskers with different doping concentration (Te) in the vicinity to the metal-insulator transition (MIT) from metal side of the transition were studied in the temperature range 1.5-60 K and magnetic field 0-14 T. Shubnikov-de Haas oscillations in GaSb whiskers at low temperatures were revealed in magnetic field range 2-12 T. The oscillation period 0.025T -1 was found at various doping concentration in GaSb whiskers. The effective mass of electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, we note that the p-type behavior of the underlying GaAs stem results from Ga vacancies as pointed out earlier. Another potential origin of ferromagnetism in our doped nanowires may lie in strong magnetic ordering of the 5p spins on the Te dopant atoms when the dopant concentration is near the MIT as suggested by Druzhinin, et al 17,18 and is the case in our samples. Coey 52 has recently discussed the complexity of temperature independent d 0 FM in oxides with non-magnetic cations and concluded that currently available data cannot be explained via our conventional understanding.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 51%
See 2 more Smart Citations
“…However, we note that the p-type behavior of the underlying GaAs stem results from Ga vacancies as pointed out earlier. Another potential origin of ferromagnetism in our doped nanowires may lie in strong magnetic ordering of the 5p spins on the Te dopant atoms when the dopant concentration is near the MIT as suggested by Druzhinin, et al 17,18 and is the case in our samples. Coey 52 has recently discussed the complexity of temperature independent d 0 FM in oxides with non-magnetic cations and concluded that currently available data cannot be explained via our conventional understanding.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 51%
“…Furthermore, the fact that ferromagnetism is observed in our doped semiconductor nanowires but not intrinsic ones suggests that it is dopant induced. We note that the doping concentration in our doped nanowires, mid-10 18 cm −3 , is in the vicinity of the metal-insulator transition (MIT) as reported by Druzhinin, et al 17,18 , which was relevant to their magnetoresistance (MR) behavior. They demonstrated that negative MR due to strong magnetic ordering occurred only when the carrier concentration of the non-magnetic Te impurities was within the MIT regime.…”
Section: Electron Energy Loss Spectroscopy Measurements(eels) Monochmentioning
confidence: 59%
See 1 more Smart Citation
“…Another, more accurate approach to describing the geometry of complex three-dimensional objects is the use of Rvachev functions, or locus [37][38][39]. The essence of this approach is that instead of the logical ratios used in the analytical expression (6), atomic functions or locus are used. Locus is smooth functions with a high value of the derivative.…”
Section: Preliminary Estimates Of the Temperature Of The Cold Cathode...mentioning
confidence: 99%
“…Then the sophisticated arithmetic-logical relation (6), taking into account (7), will be rewritten as follows:…”
Section: Set Of Functionsmentioning
confidence: 99%